SHARING KNOWLEDGE OF CREATIVITY OF SMALL AND MEDIUM BUSINESSES FACING THE CHALLENGES OF THE CONDITION OF COVID-19 - Sutrisno Sutrisno (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The main objective of this study is to find out and resolve the issues of Small and Medium-Sized Enterprises (SMEs) in Indonesia, particularly those located in Central Java's industrial sector, the northern sub-section. Primary and secondary data are used, and thereby a combination of data analysis techniques is used. The SMEs criteria are based on the Republic of Indonesia's Law No. 20 of 2008 on Micro, Small, and Medium-Sized Enterprises. According to the study's findings, SME owners were able to thrive by repackaging products, redesigning packaging, and establishing new marketing relations. This study developed the concepts of the creative knowledge sharing model, which is a synthesis of two theories, namely knowledge sharing and social identity. Keywords: Knowledge Sharing, Creativity, Social Identity, SMEs.